Pendapat Hakim PA Bangkalan dan PA Sidoarjo Mengenai Status Anak Luar Kawin - Candrawati, Siti Dalilah (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2016)
This paper is the result of a field research on the opinion of the judges of PA (Religious Church) Bangkalan and Sidoarjo against the MK’s decision No. 46/PUU-VIII/2010. The MK’s decision is important from the point of view of judge as the law enforcement because it invites a lot of debate in the community. In this research, the author collects data using interview and documentation technique. The collected data is then analyzed by using descriptive-verification technique to describe the opinion of the judges of the MK’s decision No. 46/PUU-VIII/2010. The finding of the study is that the judges of PA interpret the child outside of marital contract includes: a child born by a woman who is not tied to marriage with a man who impregnates her, a child resulted from a sirri marriage, a child born from the infidelity of either within the marital period or not, a child resulted from a living together (samen liven), a child as a result of being raped by a man or more, a child who legally denied by his father, a child as a result of a wrong sexual intercourse, a child born out of a fasid marriage, and a child born from a surrogate mother. The judges of PA also have different opinion about the MK’s decision No. 46/PUU-VIII/2010 on the legal status of a child born outside of a marital contract. There are four kinds of view: the MK’s decision is legally flawed, the MK’s decision needs a new setting, the MK’s decision has a limited effect on a materially child’s civil right, the MK’s decision has the absolute force as the first and the last constitutional court decision. Therefore, it has a legal implication for the child to his mother and father based on science and technology and/or other evidence justified by law as to have a blood relationship between a child and his biological father. [Tulisan ini merupakan hasil penelitian lapangan yang melihat pendapat hakim PA Bangkalan dan Sidoarjo terhadap putusan MK No. 46/PUU-VIII/2010. Putusan MK tersebut, penting dilihat dari sudut pandang hakim sebagai pelaksana hukum karena mengundang banyak polemik di kalangan masyarakat. Untuk itu, penulis mengumpulkan data menggunakan teknik wawancara dan dokumentasi. Data yang terkumpul kemudian dianalisis menggunakan teknik deskriptif-verifikatif untuk menggambarkan pendapat hakim tentang putusan MK No. 46/PUU VIII/2010. Dengan metode tersebut, penelitian ini menemukan, bahwa para hakim PA menginterpretasikan anak luar perkawinan meliputi: anak lahir dari perempuan yang tidak terikat perkawinan dengan laki-laki yang menghamili, anak hasil perkawinan sirri, anak lahir dari perselingkuhan baik perempuan terikat perkawinan atau tidak, anak hasil hidup bersama (samen liven), anak lahir akibat diperkosa oleh seorang laki-laki atau lebih, anak lahir yang diingkari (dili’an) ayahnya, anak lahir akibat hubungan seks salah orang/ salah sangka, anak lahir akibat perkawinan yang fa>sid/ batal, dan dimungkinkan anak lahir dari ibu pengganti (surrogate mother). Para hakim PA juga memiliki pendapat yang berbeda mengenai putusan MK No 46/PUU-VIII/2010 yang mengatur status hukum anak yang dilahirkan di luar perkawinan. Ada empat macam pandangan: putusan MK cacat yuridis, putusan MK perlu pengaturan baru, putusan MK berlaku terbatas pada hak perdata anak yang bersifat materiil, putusan MK mutlak berlaku karena merupakan putusan perkara konstitusi tingkat pertama dan terakhir, karenanya berimplikasi pada hubungan perdata anak selain dengan ibunya juga dengan ayahnya berdasarkan ilmu pengetahuan dan tehnologi dan/atau bukti lain yang dibenarkan oleh hukum memiliki hubungan darah antara anak dengan ayah biologisnya.]